2012
DOI: 10.3109/0284186x.2012.679311
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cancer patients after unplanned admission to general intensive care units

Abstract: Of the 140,154 patients with unplanned ICU admission 10.9% had a malignancy. Medical cancer patients were more severely ill on ICU admission in comparison with medical non-cancer patients, as reflected by higher needs for mechanical ventilation (50.8% vs. 46.4%, p < 0.001) and vasopressors within 24 hours after admission (41.5% vs. 33.0%, p < 0.001), higher Acute Physiology and Chronic Health Evaluation (APACHE) IV scores (88.1 vs. 67.5, p < 0.001) and a longer ICU stay (5.1 vs. 4.6 days, p < 0.001). In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
4
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 25 publications
8
52
4
8
Order By: Relevance
“…Patients with certain malignant diseases, such as esophageal cancer or acute leukemia, and those undergoing allogeneic stem cell transplantation have particularly high ICU utilization rates of up to almost 30% . Currently, patients with malignancies account for approximately 13.5% to 21.5% of all ICU admissions . In the past, patients with cancer, especially those with solid tumors, were frequently denied access to the ICU .…”
Section: Evolution Of Critical Care For Patients With Cancermentioning
confidence: 99%
“…Patients with certain malignant diseases, such as esophageal cancer or acute leukemia, and those undergoing allogeneic stem cell transplantation have particularly high ICU utilization rates of up to almost 30% . Currently, patients with malignancies account for approximately 13.5% to 21.5% of all ICU admissions . In the past, patients with cancer, especially those with solid tumors, were frequently denied access to the ICU .…”
Section: Evolution Of Critical Care For Patients With Cancermentioning
confidence: 99%
“…Previous investigations reported on the incidence of cancer and its impact on the outcome in general ICUs . These studies showed that a cancer diagnosis on admission to a general ICU is relatively common, varying between 13.5% and 21.5%, and that the outcome of these patients is strongly dependent on the type of admission, with planned surgical and unplanned medical admission types bearing the relatively best and worst prognosis, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Direct comparisons with other similar studies are difficult, with significant potential variation in intensive care admission criteria and patient population. Nevertheless, the ICU mortality in our cohort was 5%, which was consistent, if not better than seen in recent studies of similar Australian tertiary hospital ICUs, as well as internationally . Mortality at 6 months of 39% similarly compared favourably.…”
Section: Discussionmentioning
confidence: 99%